Prediction of life Satisfaction Based on Emotional Intelligence, Happiness and Religious Attitude Among Female Teachers of Urmia City, North West of Iran - Iraj Mirkhan; Iraj Shakerinia; Mousa Kafi; Nourallah Khalilzade (Shiraz University of Medical Sciences, 2014)
Background: Life satisfaction is considered to be a variable state, and not a permanent trait of the respondent but rather something present and contextual. Teachers' life satisfaction helps to improve the quality of education and create a favorable environment for the students. Objectives: This study aimed to investigate the prediction of life satisfaction based on emotional intelligence, happiness and religious attitudes among female teachers of Urmia city. Materials and Methods: The present study was a descriptive correlative research, comprised of 262 teachers of Urmia high schools. The participants were randomly selected and asked to complete the religious attitude Khodayarifard questionnaire, Oxford Happiness, Emotional intelligence Bar-On Inventory and Satisfaction with life scale Diener. Data were analyzed by the SPSS software 18 using Pearson's correlation and regression test. Results: The results showed that there is a positive relationship between emotional intelligence and life satisfaction and also a positive correlation between happiness and life satisfaction in female teachers, yet no relationship between religious attitude and life satisfaction. The results also indicated that happiness is the only determinant predicting life satisfaction. Conclusions: Our findings indicate that the components of emotional intelligence and happiness play an important role in life satisfaction of female teachers. Therefore, due to the important role of teachers in the development of any society, extensive efforts should be made to improve their life satisfaction.